PENGARUH VARIASI NAUNGAN DAN KONSENTRASI IBA (Indole Butyric Acid) TERHADAP KEBERHASILAN SAMBUNG SAMPING TANAMAN JAMBU AIR CITRA (Syzygium samarangense) - Adjeng Setia Ningtyas; Karno Karno; Syaiful Anwar (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2023)
This research aimed was to determine the effect of variations in shade and concentration of IBA on the success of side grafting of water apple var. Citra (Syzygium samarangense). The design used in this study was a 3 x 4 Split Plot Design based on a Completely Randomized Design (CRD). The first factor was the variation of shade which was placed as the main plot with 3 treatment levels (40%, 60%, and 80%). The second factor was the concentration of IBA as sub-plots with 4 treatment levels (0 ppm, 75 ppm, 100 ppm, and 125 ppm). Each treatment was repeated 3 times to produce 36 experimental units and each experimental unit consisted of 8 plants. Parameters observed included the percentage of live seedlings, shoot emergence time, shoot length, number of leaves, leaf length, and crown width. The data obtained were analyzed statistically using analysis of variance (ANOVA) and further tested with the DMRT (Duncan's Multiple Range Test) with a level of 5%. The results showed that the shade variation treatment had a significant effect on the parameters of shoot emergence time, shoot length, and a number of leaves. The administration of IBA at various concentration levels did not have a significant effect on all parameters. There was no interaction effect between the treatment of variations in shade and concentration of IBA on the success of side grafting of water apples. The conclusion of this research was the use of shade 40% and 60% was the right level in the process of side grafting of water apples. The addition of 75 ppm, 100 ppm and 125 ppm IBA did not affect the success of side grafting of water apple